Mozambique’s private sector in the context of conflict - Macuane, José Jaime (International Growth Centre, 2018)
This case study analyses the interactions between conflict and private sector development in Mozambique. In the 42 years following its independence, Mozambique faced a 16-year civil war from 1976/77 to 1992, an interim period of peace that lasted 20 years, and recurring, low-level conflict involving the same belligerents since 2013. This case study examines the conflict dynamics in post-independence Mozambique, and how the private sector has developed in response to both conflict and peace.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; conflict / conflito; private sector / setor privado